The effect of topical aloe vera and breast milk on the recovery of cracked nipples - Fazdria, Fazdria; Alchalidi, Alchalidi; Kasad, Kasad; Faisal, T. Iskandar (Institute of Computer Science (IOCS), 2025)
One of the common discomforts during the postpartum period is cracked nipples. If not properly managed, this condition may lead to mastitis. This study aimed to analyze the effect of topical application of aloe vera and breast milk on the healing of cracked nipples. This research employed a quasi-experimental design with a two-group pretest–posttest approach. The sample consisted of 34 postpartum mothers with cracked nipples at Birem Bayeun Community Health Center. Data were analyzed using the Wilcoxon test. The results showed a significant effect of aloe vera and breast milk application on the healing of cracked nipples (p = 0.000). It can be concluded that the topical application of aloe vera and breast milk has a significant effect on the recovery of cracked nipples among postpartum mothers.